History and Culture: A Critical literature review on Britishness - Wang, Yuanyuan (Journal of Theory and Practice in Humanities and Social Sciences, 2024)
This critical literature review investigates the concept of “Britishness” from the 19th century to the present, examining its evolution and the debates that have emerged around it through the lenses of physical landscapes, historical heritage, and British literary works. It differentiates between “Britishness” and “Englishness,” emphasizing the inclusive nature of the former and its imperial roots. Moreover, the review underscores the complexities involved in defining Britishness, its historical significance, and its representation in literature, all of which serve as reflections of national identity and values.